FUNGSI MUSEUM SIMALUNGUN SEBAGAI SUMBER MEDIA PEMBELAJARAN IPS BAGI SISWA SISWI KELAS VIII A MTs MESRA KOTA PEMATANGSIANTAR T.A 2023/2024 - Ahmad Abdillah Syahfitra; Andres M. Ginting; Asnewastri (Prodi Pendidikan Sejarah FKIP USI, 2026)
Museums were initially only a gathering place and often also used as a place of reflection, over time they have changed into a place of reference, learning and education. As the museum has developed into a source of learning. Learning can be defined as a form of cooperation between teachers and students in utilizing learning resources. With the increasingly developing era, anything that can provide knowledge is a learning resource, one of which is a museum, which in this study, the Simalungun Museum is the object of this study. The Simalungun Museum is expected to be an interesting learning resource for students of MTs Mesra Pematangsiantar City which then makes students' creativity, activeness and way of thinking increase. The purpose of this study is to see how to function the museum as a learning resource media for History Social Studies. This study also shows that the results of functioning the Simalungun Museum as a learning resource for History Social Studies are agreeable. This can be seen from the results of the questionnaire distributed showing a figure of 76.94%. As well as the results of the interview stated that they agreed that functioning the Simalungun Museum as a learning resource media for Social Studies. This shows that the Simalungun Museum has a good function in increasing students' interest in learning social studies subjects.